Human papillomavirus type 16 E7 promotes cell viability and migration in cervical cancer by regulating the miR-23a/HOXC8 axis - Yahang Chen; Lei Sun; Lin Li (Journal of Obstetrics and Gynaecology)
Background Human papillomavirus (HPV) is a risk factor for the occurrence of cervical cancer (CC). Here, we aimed to explore the role of HPV16 in CC and identify the underlying mechanism.Methods The expression of miR-23a, HPV16 E6/E7 and homeobox C8 (HOXC8) was measured by quantitative real-time PCR or western blot. Cell viability and migration were evaluated using cell counting kit-8, Transwell and wound healing assays. The targeting relationship between miR-23a and HOXC8 was revealed by dual-luciferase reporter assay.Results miR-23a was downregulated in HPV16-positive (HPV16+) CC tissues and HPV16+ and HPV18+ cells. Additionally, E6/E7 expression was increased in CC cells. Then, we found that E7, rather than E6, positively regulated miR-23a expression. miR-23a suppressed cell viability and migration, whereas E7 overexpression abrogated this suppression. miR-23a targeted HOXC8, which reversed miR-23a-mediated cell viability and migration.Conclusions HPV16 E7-mediated miR-23a suppressed CC cell viability and migration by targeting HOXC8, suggesting a novel mechanism of HPV-induced CC.